Infancy onset diabetes mellitus in a patient with a novel homozygous LRBA mutation - Iman Hawari (12561958) (2022)
Background LRBA deficiency is associated with common variable immune deficiency which manifests as hypogammaglobulinemia, autoimmunity, antibodies deficiency, lymphoproliferation and a high susceptibility to inflammatory bowel disease in early childhood. Diabetes mellitus, growth retardation and short stature have also been reported in some patients with LRBA deficiency Methodology The proband with infancy-onset diabetes mellitus was recruited with her family. Glutamic acid decarboxylase, insulin, protein tyrosine phosphatase and zinc transporter autoantibodies were measured. Whole genome sequencing for the proband was undertaken to identify causative gene and candidate mutations were confirmed using Sanger sequencing. A diagram of LRBA with predicted domains and reported mutations of LRBA in patients diagnosed with diabetes mellitus was used to investigate clinical phenotype relation to genotype in this type of patients. Results Here we report a novel homozygous mutation in LRBA (W1330*, c.3999 G > A) in a child diagnosed with immunodeficiency and infancy-onset diabetes mellitus at the age of 7 months. The same mutation was also found in an older sibling but that sibling does not have diabetes mellitus. The heterogeneity of diabetes presentation in LRBA-deficient patients suggests other genetic factors or protein-protein interactions in the LRBA pathway may play a role in the pathogenesis of the disease Other Information Published in: Journal of Clinical and Translational Endocrinology: Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jecr.2022.100108